Characteristics and outcomes of rapid response team activations for hypotension in orthopaedic patients. Issue 1 (14th January 2020) - Ramos, João G. R.; Zhang, Richard; Maher, Brendan; Hardidge, Andrew; Weinberg, Laurence; Robbins, Ray; Peyton, Phillip J.; Bellomo, Rinaldo; Jones, Daryl
Abstract: Background: Hypotension following orthopaedic surgery has been associated with increased morbidity and mortality. Rapid response teams (RRT) review patients on hospital wards with hypotension. Aim: To evaluate the epidemiology of hypotensive RRT activations in adult orthopaedic patients to identify contributing factors and areas for future quality improvement. Methods: Timing of RRT activations, presumed causes of hypotension and associated treatments were assessed. Results: Among 963 RRT activations in 605 patients over 3 years, the first calls of 226 of 605 patients were due to hypotension, and 213 (94.2%) of 226 had sufficient data for analysis. The median age was 79 (interquartile range 66–87) years; 58 (27.2%) were male, and comorbidities were common. Most (68%) surgery was emergent, and 75.1% received intraoperative vasopressors for hypotension. Most activations occurred within 24 h of surgery, and hypovolaemia, infection and arrhythmias were common presumed causes. Fluid boluses occurred in 173 (81.2%), and the time between surgery and RRT activation was 10 (4.0–26.5) h. in cases where fluid boluses were given, compared with 33 (15.5–61.5) h. where they were not ( P < 0.001). Blood transfusion (30, 14.1%) and withholding of medications were also common. Hospital mortality was 8.5% (18), and 13.6% (29) were admitted to critical care at some stage. In‐hospital death was associated with older age, functional dependence, arrhythmia and presumed infection. Conclusions: Hypotension‐related RRT calls in orthopaedic patients are common. Future interventional studies might focus on perioperative fluid therapy and vaso‐active medications, as well as withholding of anti‐hypertensive medications preoperatively.